"Anarchy all over Baščaršija": Yugoslavia's new socialist culture and the New Primitives poetics of the local. Issue 2 (27th June 2012) - Mišina, Dalibor
Abstract: The paper analyses Sarajevo's music movement of New Primitives and its "poetics of the local" as a struggle against the cultural hypocrisy of Yugoslavia's "new socialist culture" and its privileging of "external‐cosmopolitan" as apotheosis of cultured refinement and sophistication while denigrating "local‐parochial" as epitome of uncultured primitiveness. I argue that the movement's praxis is best understood as a call to reject externally‐imposed frames of reference as the basis for self‐understanding, and to embrace a socio‐cultural awareness that the only way to be in the world is to be authentically "primitive"– i.e. to exist as a distinct and autochthon socio‐cultural self.